2016
DOI: 10.3945/ajcn.115.118612
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein intake is associated with body mass index and weight up to 5 y of age in a prospective cohort of twins

Abstract: Background: Few large epidemiologic studies have investigated the role of postweaning protein intake in excess weight and adiposity of young children, despite children in the United Kingdom consistently consuming protein in excess of their physiologic requirements.Objective: We investigated whether a higher proportion of protein intake from energy beyond weaning is associated with greater weight gain, higher body mass index (BMI), and risk of overweight or obesity in children up to 5 y of age.Design: Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 32 publications
4
80
0
4
Order By: Relevance
“…Conversely, there was clear reduction in key regulators of the lipid oxidation process, including PGC‐1α, SIRT3, ACAA2, and HADHSC in RedTg livers. It has been previously reported that ad libitum‐fed animals on diets that are high in carbohydrates, but low in proteins, have greater adiposity and the longest lifespan (Solon‐Biet et al., 2014), although the association between the intake of protein/carbohydrates and adiposity is still a matter of debate (Fontana et al., 2016; Maida et al., 2016; Solon‐Biet et al., 2015) including prospective cohort studies of humans (Berryman, Agarwal, Lieberman, Fulgoni & Pasiakos, 2016; Pimpin, Jebb, Johnson, Wardle & Ambrosini, 2016). Nonetheless, the maintenance of body weight in older RedTg mice may be due to higher fat accumulation than in Wt controls, in agreement with our recent study that showed a positive correlation between mouse longevity and conservation of body fat (Mitchell et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, there was clear reduction in key regulators of the lipid oxidation process, including PGC‐1α, SIRT3, ACAA2, and HADHSC in RedTg livers. It has been previously reported that ad libitum‐fed animals on diets that are high in carbohydrates, but low in proteins, have greater adiposity and the longest lifespan (Solon‐Biet et al., 2014), although the association between the intake of protein/carbohydrates and adiposity is still a matter of debate (Fontana et al., 2016; Maida et al., 2016; Solon‐Biet et al., 2015) including prospective cohort studies of humans (Berryman, Agarwal, Lieberman, Fulgoni & Pasiakos, 2016; Pimpin, Jebb, Johnson, Wardle & Ambrosini, 2016). Nonetheless, the maintenance of body weight in older RedTg mice may be due to higher fat accumulation than in Wt controls, in agreement with our recent study that showed a positive correlation between mouse longevity and conservation of body fat (Mitchell et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Além das DCVs, as dislipidemias, hipertensão arterial e hiperglicemia têm sido observadas (22) . Os mesmos possuem alto teor de sódio e de lipídeos, e em nada acrescentam a alimentação infantil, trazendo como consequências o aumento de peso e anemia ferropriva (8,(20)(21) .…”
Section: Discussionunclassified
“…A obesidade acarreta complicações orgânico-funcionais, como doenças crônico-degenerativas (diabetes, hipertensão arterial, doenças coronarianas), e psicossociais, como afastamento das relações sociais, vergonha, exclusão e distúrbios na consciência corporal (8) . A obesidade é considerada um problema de saúde pública mundial; no caso das crianças, nos últimos 10 anos, houve um aumento de 40% nos índices de obesidade infantil (9) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The association of introduction of complementary foods and body composition in childhood was assessed in some studies [17][18][19] . Although there is scant evidence regarding introduction of complementary foods and body composition on later periods such adolescence and adulthood based on prospective studies [20].…”
Section: Introductionmentioning
confidence: 99%